What are health disparities and health equity? We need to be clear - Braveman, Paula (Public health reports (1974), 2014)
"Health disparities" and "health equity" have become increasingly familiar terms in public health, but rarely are they defined explicitly. Ambiguity in the definitions of these terms could lead to misdirection of resources. This article discusses the need for greater clarity about the concepts of health disparities and health equity, proposes definitions, and explains the rationale based on principles from the fields of ethics and human rights."Health disparities" and "health equity" have become increasingly familiar terms in public health, but rarely are they defined explicitly. Ambiguity in the definitions of these terms could lead to misdirection of resources. This article discusses the need for greater clarity about the concepts of health disparities and health equity, proposes definitions, and explains the rationale based on principles from the fields of ethics and human rights.